2019 IEEE Information Theory Workshop (ITW) 2019
DOI: 10.1109/itw44776.2019.8989272
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Quasi-Maximum Likelihood Decoding of Short LDPC Codes Based on Saturation

Abstract: In this paper, we propose an enhanced quasimaximum likelihood (EQML) decoder for LDPC codes with short block lengths. After the failure of the conventional belief propagation (BP) decoding, the proposed EQML decoder selects unreliable variable nodes (VNs) and saturates their associated channel output values to generate a list of decoder input sequences. Each decoder input sequence in the list is then decoded by the conventional BP decoder to obtain the most likely codeword. To improve the accuracy of selecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For irregular LDPC codes, the same conclusion can be drawn by substituting L × S dv−1 with L × S D v . This indicates that the RFs defined by (17) lead to an information optimum Q v with sufficiently large q v .…”
Section: B Mim-qbp Decoder Design At Vn For Irregular Ldpc Codesmentioning
confidence: 88%
See 3 more Smart Citations
“…For irregular LDPC codes, the same conclusion can be drawn by substituting L × S dv−1 with L × S D v . This indicates that the RFs defined by (17) lead to an information optimum Q v with sufficiently large q v .…”
Section: B Mim-qbp Decoder Design At Vn For Irregular Ldpc Codesmentioning
confidence: 88%
“…From (17), we observed that |φ ch | max + d v,max |φ v | max can be much smaller than 2 qv−1 − 1 especially for initial decoding iterations, where…”
Section: B Dynamic Reconstructionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bit-flip means that the priori knowledge of the flipped information bit is set to infinity, i.e., if u i is flipped to 0, then the so-called R message of u i is set to plus infinity, and vice versa. Note that in LDPC codes, there exist bit saturation methods [18]- [20] that set the initial channel LLRs of variable nodes to infinity for better BLER performance. However, in this paper, we flip the priori knowledge of information bits, not that of variable nodes.…”
Section: Introductionmentioning
confidence: 99%